Mixed Epithelial and Stromal Tumor of the Kidney or Adult Mesoblastic Nephroma : An Update - Moslemi, Mohammad Kazem (Urology Journal, 2010)
PURPOSE: Our aim was to review the spectrum of usual and unusual clinical and morphologic findings observed in mixed epithelial and stromal tumor of the kidney (MEST). MATERIALS AND METHODS: On the basis of MEDLINE database searches, we assessed all aspects of MEST or adult mesoblastic nephroma since the first report in 1997 till the end of 2009. RESULTS: Mixed epithelial and stromal tumor is a relatively rare and distinct neoplasm of the kidney that should be distinguished from other renal neoplasms. Although the overall prognosis is favorable, recurrence andmalignant transformation of MEST can occur CONCLUSION: It is difficult to distinguish benign or malignant nature onimaging studies.